Characterization of fungus‐specific microsatellite markers in the lichen‐forming fungus Parmelina carporrhizans (Parmeliaceae)1. (20th November 2014) - Alors, David; Dal Grande, Francesco; Schmitt, Imke; Kraichak, Ekaphan; Lumbsch, H. Thorsten; Crespo, Ana; Divakar, Pradeep K.
Abstract : Premise of the study: Microsatellite loci were developed to study the lichen‐forming fungus Parmelina (Parmeliaceae) in different habitats of western Europe and the Mediterranean for baseline studies to understand the effects of climate change on its distribution. Methods and Results: We cultured P. carporrhizans from ascospores for genomic sequencing with Illumina HiSeq. We successfully developed 11 polymorphic microsatellite markers and associated primer sets and assessed them with 30 individuals from two of the Canary Islands. The average number of alleles per locus was 8.8. Nei's unbiased gene diversity of these loci ranged from 0.53 to 0.91 in the tested populations. Amplification in two closely related species ( P. tiliacea, P. cryptotiliacea ) yielded only limited success. Conclusions: The new microsatellite markers will allow the study of genetic diversity and population structure in P. carporrhizans . We propose eight markers to combine in two multiplex reactions for further studies on a larger set of populations.